Hypoxic Regulation of the Large-Conductance, Calcium and Voltage-Activated Potassium Channel, BK - Ochoa, Sara V.; Otero, Liliana; Aristizabal-Pachon, Andres Felipe; Hinostroza, Fernando; Carvacho, Ingrid; Torres, Yolima P. (Frontiers in Physiology, 2021)
Hypoxia is a condition characterized by a reduction of cellular oxygen levels derived from alterations in oxygen balance. Hypoxic events trigger changes in cell-signaling cascades, oxidative stress, activation of pro-inflammatory molecules, and growth factors, influencing the activity of various ion channel families and leading to diverse cardiovascular diseases such as myocardial infarction, ischemic stroke, and hypertension. The large-conductance, calcium and voltage-activated potassium channel (BK) has a central role in the mechanism of oxygen (O2) sensing and its activity has been related to the hypoxic response. BK channels are ubiquitously expressed, and they are composed by the pore-forming α subunit and the regulatory subunits β (β1–β4), γ (γ1–γ4), and LINGO1. The modification of biophysical properties of BK channels by β subunits underly a myriad of physiological function of these proteins. Hypoxia induces tissue-specific modifications of BK channel α and β subunits expression. Moreover, hypoxia modifies channel activation kinetics and voltage and/or calcium dependence. The reported effects on the BK channel properties are associated with events such as the increase of reactive oxygen species (ROS) production, increases of intracellular Calcium ([Ca2+]i), the regulation by Hypoxia-inducible factor 1α (HIF-1α), and the interaction with hemeproteins. Bronchial asthma, chronic obstructive pulmonary diseases (COPD), and obstructive sleep apnea (OSA), among others, can provoke hypoxia. Untreated OSA patients showed a decrease in BK-β1 subunit mRNA levels and high arterial tension. Treatment with continuous positive airway pressure (CPAP) upregulated β1 subunit mRNA level, decreased arterial pressures, and improved endothelial function coupled with a reduction in morbidity and mortality associated with OSA. These reports suggest that the BK channel has a role in the response involved in hypoxia-associated hypertension derived from OSA. Thus, this review aims to describe the mechanisms involved in the BK channel activation after a hypoxic stimulus and their relationship with disorders like OSA. A deep understanding of the molecular mechanism involved in hypoxic response may help in the therapeutic approaches to treat the pathological processes associated with diseases involving cellular hypoxia.